Which whitening toothpaste with different contents is more effective on color and bond strength of enamel? - Dursun, Meltem Nermin; Ergin, Esra; Tekce, Aybuke Uslu; Gurgan, Sevil (Wiley, 2023)
Objective To evaluate the effects of six whitening toothpastes with different whitening ingredients as follows: abrasives, polyphosphates, activated charcoal and hydrogen peroxide on the color, and shear bond strength (SBS) of enamel. Materials and Methods Thirty-five extracted human molars were sectioned in mesiodistal direction, providing 70 enamel specimens and randomly divided into seven groups having different whitening ingredients (n = 10). After baseline color measurements, the specimens were brushed three times daily for the 30 s. At the end of 2 weeks, spectrophotometric readings were repeated, and color change parameters were calculated. Then, composite cylinders were built on the enamel surfaces and the specimens were subjected to SBS test. Failure modes were determined under a stereomicroscope (x10). One specimen from each group was examined with scanning electron microscope (SEM). The data were statistically analyzed using Kruskal-Wallis, Wilcoxon signed, one-way-ANOVA (p = 0.05). Results Clinically acceptable color change was observed in all whitening toothpastes. There were no significant differences among the groups for Delta a, Delta L, Delta E-00, and Delta WID (p > 0.05). The differences among the groups were not significant regarding SBS and failure mode distributions (p > 0.05). SEM findings were in line with the SBS test and failure mode distribution results. Conclusions All the tested whitening toothpastes showed similar and clinically acceptable efficacy on the color change of the enamel and led to comparable SBS values. Clinical Significance The tested whitening toothpastes had an acceptable whitening efficacy and did not have a negative effect on the bond strength to the enamel.
Keywords: color; dentistry; enamel; shear bond strength; toothbrushing; toothpastes; whitening